2018
DOI: 10.1177/0961203318817118
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal disease in patients with systemic lupus erythematosus from Southern China: a retrospective study

Abstract: Objective To investigate the characteristics and associated factors of invasive fungal disease in patients with systemic lupus erythematosus from Southern China. Methods A retrospective study was performed. Demographic and clinical characteristics, laboratory data, and radiographic manifestations were recorded. Results A total of 45 lupus patients with invasive fungal disease (incidence 1.1%) were included. Twenty-three cases (51.1%) were infected with mold and 22 cases (48.9%) with yeast. Aspergillus spp. (44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
14
0
6
Order By: Relevance
“…Superficial mycosis, commonly known as ringworm, is a common infectious disease in dermatology caused by pathogenic fungi parasitic on keratin tissue (1,2). Its incidence rate is increasing year by year (3). In recent years, with the wide application of broad-spectrum antibiotics, glucocorticoids, immunosuppressants and anti-tumor drugs, the possibility of secondary fungal infection in patients has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Superficial mycosis, commonly known as ringworm, is a common infectious disease in dermatology caused by pathogenic fungi parasitic on keratin tissue (1,2). Its incidence rate is increasing year by year (3). In recent years, with the wide application of broad-spectrum antibiotics, glucocorticoids, immunosuppressants and anti-tumor drugs, the possibility of secondary fungal infection in patients has increased.…”
Section: Introductionmentioning
confidence: 99%
“…In our research, the incidence of IM was the highest in AAV (1.5%), compared to 0.5% in the SLE population [22]. Charles et al reviewed 80 patients with AAV treated with rituximab and found three cases of aspergillosis (3.8%) [23].…”
Section: Discussionmentioning
confidence: 73%
“…Our results further supported the previous finding and showed that accumulated dose of GC was associated with the development of cryptococcosis in patients with CTD. Other risk factors such as lymphopenia, hypoalbuminemia which were associated with aspergillosis [27] seemed to be less relevant in cryptococcosis.…”
Section: Discussionmentioning
confidence: 95%